If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(x + 7) = -36 Reorder the terms: 2(7 + x) = -36 (7 * 2 + x * 2) = -36 (14 + 2x) = -36 Solving 14 + 2x = -36 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-14' to each side of the equation. 14 + -14 + 2x = -36 + -14 Combine like terms: 14 + -14 = 0 0 + 2x = -36 + -14 2x = -36 + -14 Combine like terms: -36 + -14 = -50 2x = -50 Divide each side by '2'. x = -25 Simplifying x = -25
| 2xy=0.02 | | 3x-4y=-6 | | 25y^2+16=0 | | 6(x+1)+3(2-x)=2(2x-1)-(4-x) | | 3*0-4y=-6 | | p^2-50=0 | | 0.01=(1-x)x | | (5x-1)+(13-x)=24 | | x^2+5=9-6x+x^2 | | 4d^2+81=0 | | -3x=2y | | y-6=0.5x | | 0.18(12)+0.03x=0.09(24+x) | | 3(4x-3)-19=8x-4 | | -(x+3)+(2x-1)=(1+4x)+(3+x) | | -6+2x=20 | | a^2+1=0 | | -20+7x=-118 | | -9-2x=9 | | 4(5x-10)=20(x-20) | | 44+9x=125 | | -1(8+x)=7 | | 6t^2-5=0 | | -4x-22=14 | | -2(x+3)+4(2x+3)=-6 | | -4x+9=53 | | -23-10x=77 | | -72-9x=63 | | 49b^2-40=-21b | | 4+7(x-11)=-59 | | -19-3x=-61 | | -43+8x=101 |